Marketing Communication Strategy Analysis at Slice Coffee Medan in Attracting Customer Interest - Fahrunissa, Abhinaya Rizki; Syam, Abdi Mubarak (Journal Analytica Islamica, 2025)
In response to the growing competition within the culinary industry in Medan, this study aims to analyze the marketing communication strategy implemented by Slice Coffee Medan in attracting customer interest and fostering brand loyalty. The research focuses on identifying the core components of Slice Coffee's marketing communication, evaluating their effectiveness, and understanding their impact on consumer behavior and purchasing decisions. A qualitative case study approach was employed, utilizing in-depth interviews with the café’s management and customers, surveys, and on-site observations. These methods enabled a comprehensive understanding of how the café leverages digital platforms—particularly Instagram and TikTok—visual aesthetics, targeted promotional campaigns, and two-way interactive engagement to shape customer perceptions. Data triangulation, member checking, and audit trails were applied to ensure research validity. The findings reveal that Slice Coffee’s integrated strategy—highlighted by campaigns such as the “Slice Signature Challenge”—successfully transforms customers into brand advocates, with measurable outcomes including a 32% increase in new visits and a 25% rise in customer return rate within six months. Additionally, the café’s focus on visual storytelling and customer-centric interaction has resulted in strong brand recall and emotional attachment among its core demographic of young, digitally active consumers. This study concludes that an integrated and interactive marketing communication strategy, when aligned with customer preferences and supported by consistent branding efforts, can significantly enhance brand competitiveness and sustainability. The results offer both theoretical contributions to the field of marketing communication and practical recommendations for coffee shop businesses in the digital era.